Reserve of harmonic functions of the infinite number of variables. III - Feller , M. N. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We obtain optimal (in a certain sense) harmonicity conditions on functions on a Hilbert space which follow from estimates for sums of independent random variables. Together with the harmonicity conditions obtained earlier, based on estimates of the order of growth for sums of dependent random variables and for sums of orthogonal random variables, they make it possible to consider new classes of harmonic functions of an infinite number of variables.